2017
DOI: 10.1101/186890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of DISE-inducing shRNAs by monitoring cellular responses

Abstract: Off-target effects (OTE) are an undesired side effect of RNA interference (RNAi) caused by partial complementarity between the targeting siRNA and mRNAs other than the gene to be silenced. The death receptor CD95 and its ligand CD95L contain multiple sequences that when expressed as either si-or shRNAs kill cancer cells through a defined OTE that targets critical survival genes. Death induced by survival gene elimination (DISE) is characterized by specific morphological changes such as elongated cell shapes, s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…679 3) Are there other genes in the human genome containing toxic seed sequences? We recently 680 identified other genes in the genome that contain DISE inducing shRNAs (Patel & Peter, 2017). 681…”
Section: The Role Of Dicer In Dise 649mentioning
confidence: 99%
“…679 3) Are there other genes in the human genome containing toxic seed sequences? We recently 680 identified other genes in the genome that contain DISE inducing shRNAs (Patel & Peter, 2017). 681…”
Section: The Role Of Dicer In Dise 649mentioning
confidence: 99%
“…We recently reported that si‐ and shRNAs derived from CD95, CD95L , and other genes in the human genome kill cancer cells through RNAi by targeting a network of critical survival genes . DISE (death induced by survival gene elimination) was found to involve simultaneous activation of multiple cell death pathways, and cancer cells have a hard time developing resistance to this form of cell death .…”
Section: Introductionmentioning
confidence: 99%